Processing wood into a phase change material with high solar-thermal conversion efficiency by introducing stable polyethylene glycol-based energy storage polymer. (1st September 2022) - Li, Yanchen; Wang, Beibei; Zhang, Weiye; Zhao, Junqi; Fang, Xiaoyang; Sun, Jingmeng; Xia, Rongqi; Guo, Hongwu; Liu, Yi
Abstract: Wood is widely used in the field of building materials as a green and renewable natural porous material. With the continuous increase of global carbon dioxide emissions and increasingly serious environmental problems, improving the energy storage performance of wood is conducive to reduce carbon dioxide and regulate the temperature of the living environment. In this work, a composite phase change material is prepared by introducing stable polyethylene glycol-based energy storage polymer (PGMA) into the porous structure of delignified wood by high temperature immersion method. The wood structure has a greater influence on the crystallinity of PGMA and the modifier is widely distributed inside the lumen and also the cell wall, with crystallinity of 90% PGMA-Wood up to 8.97% and it exhibits good dimensional stability at high temperature. The thermal conductivity of 90% PGMA-Wood is increased to 0.32W/m·K, which reaches 190% higher than that of original wood for the lattice heat transfer replaces phonon heat transfer. The phase change temperature of 90% PGMA-Wood meets the comfortable indoor temperature for human with the melting enthalpy and solidification enthalpy are 25.12 J/g and 31.59 J/g, respectively. The simulated sunlight experiment shows that under the same lighting conditions, the indoor temperature of the house model made by 90% PGMA-Wood is 3 °C higher than that of the house made of original wood, which also has stronger thermal insulation performance at low temperature. All above indicates that PGMA-Wood have great potential applications in the field of solar-thermal energy conversion and storage as building insulation board and agricultural greenhouses. Graphical abstract: Image 1 Highlights: Green energy storage technology of wood. Synthesis of a stable PEG-based phase change energy storage material to prevent PEG leakage. PCES-Wood shows high phase change enthalpy and high thermal conductivity. PCES-Wood shows good photothermal conversion efficiency and long-term thermal insulation performance.